2007
DOI: 10.1158/0008-5472.can-07-2119
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2 Deficiency Decreases ras/CDK4-Dependent Malignant Progression, but Not myc-Induced Tumorigenesis

Abstract: We have previously shown that forced expression of CDK4 in mouse skin (K5CDK4 mice) results in increased susceptibility to squamous cell carcinoma (SCC) development in a chemical carcinogenesis protocol. This protocol induces skin papilloma development, causing a selection of cells bearing activating Ha-ras mutations. We have also shown that myc-induced epidermal proliferation and oral tumorigenesis (K5Myc mice) depends on CDK4 expression. Biochemical analysis of K5CDK4 and K5Myc epidermis as well as skin tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…This is consistent with the observation that malignant transformation of human cells requires hTERT, oncogenic Ras, st expression, and inactivation of the p53 and pRB pathways (51). Considering that activated Ras cooperates with cyclin E in the transformation of rodent fibroblasts (53) and that Ras-CDK4-dependent tumorigenesis in the mouse skin is susceptible to CDK2 ablation (49), it is possible that full malignant transformation by coexpression of cyclin E and st in NHF requires alterations in Ras signaling. In regard to the selectivity between cooperating oncogenes, it is also important to note that st did not cooperate with cyclin D1 to induce mitogenic independent cell cycle entry (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the observation that malignant transformation of human cells requires hTERT, oncogenic Ras, st expression, and inactivation of the p53 and pRB pathways (51). Considering that activated Ras cooperates with cyclin E in the transformation of rodent fibroblasts (53) and that Ras-CDK4-dependent tumorigenesis in the mouse skin is susceptible to CDK2 ablation (49), it is possible that full malignant transformation by coexpression of cyclin E and st in NHF requires alterations in Ras signaling. In regard to the selectivity between cooperating oncogenes, it is also important to note that st did not cooperate with cyclin D1 to induce mitogenic independent cell cycle entry (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, CDK2 knockdown or pharmacologic inhibition specifically inhibits human melanoma cell proliferation and colony formation, indicating that CDK2 activity is required in certain human cancers (47), despite being dispensable for proliferation of other human tumor cells (48). Moreover, in mouse Ras-dependent skin tumorigenesis models where CDK4 expression is driven by a tissue specific promoter, ablation of CDK2 results in decreased incidence and multiplicity of skin tumors (49). In contrast, CDK2 ablation does not affect the incidence of c-Myc-induced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, high-throughput screens have previously uncovered synthetic lethal interactions between oncogenic KRAS and several CDKs, including CDK1, CDK2 and CDK6 (Barbie et al, 2009). Moreover KRAS -mutant tumors were shown to be more sensitive to CDK inhibition than KRAS-wild-type tumors (Macias et al, 2007; Puyol et al, 2010), which might explain their increased sensitivity to miR-214-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cdk2 is known to have a critical role in melanoma growth (32), and deregulated expression of cyclin E is observed in many cancers and correlates with poor outcome, for instance, in breast cancer (33). Of course this does not necessarily mean that cyclin E/Cdk2 is essential for all tumors or even for all Myc-driven tumors (34,35), because it is possible that in addition to its role in senescence, other functions of Myc, including its stimulation of apoptosis, are rate-limiting for the development of some tumors. Goga et al (36) recently reported that pharmacological inhibition of Cdk1 enhances Myc-induced apoptosis by targeting the antiapoptotic protein survivin.…”
Section: Discussionmentioning
confidence: 99%